The Implementation of English Morning Activity for Teachers - Muhammad Alfarizi; Adib Ahmada (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The purpose of this study was to identify and analyze various strategies implemented in this program and their impact on teachers' communication skills. This study used a qualitative approach with a case study method in several schools that have implemented English Morning Activity. Data collection techniques include in-depth interviews with teachers, activity observations, and analysis of related documents. The data obtained were analyzed thematically to identify patterns in program implementation and factors that support its success. The results showed that the main strategies in English Morning Activity include English Morning Meetings, Clubs, English of the Day, and the use of the WhatsApp application as a medium for communication and practice. This strategy has proven effective in increasing self-confidence, speaking fluency, and forming more natural English language habits in the school environment. In addition, a technology-based approach provides flexibility for teachers to continue practicing outside of working hours. Overall, this study confirms that the combination of various strategies in English Morning Activity can create a more conducive learning environment, support teacher professional development, and strengthen the culture of speaking English in schools.